What is the evidence base for integrating health and environmental approaches in the school context to nurture healthier and more environmentally aware young people? A systematic scoping review of global evidence - Proctor, Rachel; Guell, Cornelia; Wyatt, Katrina; Williams, Andrew James (Health & Place, 2020)
This scoping review collates empirical and gray literature that examines how schools are acting to nurture healthier and more environmentally aware young people through integrated approaches. Over the last twenty years, integration has been increasing within school contexts. Approaches include teaching and learning, physical environmental adaptations, developing ecologically focused policy, and reorienting wider school culture. We noted a developing discourse around what constitutes evidence in this emerging interdisciplinary field. Developing a better understanding of integrated approaches and an evidence base of what works and how could inform interdisciplinary collaboration and enable a clearer message to be communicated to stakeholders about how the school context can nurture healthier and more environmentally aware young people.
Keywords: Education; Environment; Health; School; Scoping review; Sustainability